The Effect of Using Computer Technology on English Language Teachers’ Performance in Secondary Schools : أثر استخدام تكنولوجيا الحاسوب في اللغة الإنجليزية أداء المعلمين في المدارس الثانوية (مجلة ديالى للبحوث الانسانية, 2022)
The study aims to show  the positive side of technology on the Iraqi teachers’ performance in the process of English as foreign language. The  method that depends in this study is the descriptive method. The data collected by the questionnaire paper which was pointed for English language teachers in Wasit  province who represent the sample of this study. The respondents consist both gender so they  are about 70 English language teachers in secondary schools. In order to show the percentage of  questionnaire the data which obtains was analyzed by using (Excel) program. The main results tells high percentage of them have affirmative attitudes for integrating computer technology in process of  teaching EFL classroom. Also the study shows that more of English teachers don’t have  enough trained to use the new technology tools in  English lesson as well as these tools like computers aren’t available in generality of Wasit schools. The study recommends that English teachers have to motivate about using computers skills which facilitate to the process of integrate the technology with learning.